2012
DOI: 10.3409/fb60_1-2.17-25
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability and Changes of Elemental Concentrations in Cells of Tetrix tenuicornis (Orthoptera: Tetrigidae) from Polluted and Unpolluted Areas

Abstract: GRZYWACZ B., WARCHA£OWSKA-LIWA E, BANACH Z., PYZA E. 2012. Genetic variability and changes of elemental concentrations in cells of Tetrix tenuicornis (Orthoptera: Tetrigidae) from polluted and unpolluted areas. Folia biologica (Kraków) $: 17-25.Genetic variability between populations of the orthopteran insect Tetrix tenuicornis, collected from six locations in Poland, was assayed by using the random amplified polymorphic DNA-polymerase chain reaction (RAPD-PCR) method. The results show that insects in a popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…It has been documented that populations exposed to heavy metal pollution can exhibit varying responses, leading to either an increase or decrease in their genetic variation. An illustrative case can be found in the long-horned groundhopper, Tetrix tenuicornis (Sahlberg) (Orthoptera: Tetrigidae), where individuals collected from metal-polluted regions in Boleslaw, Poland, displayed reduced genetic variability compared to populations from unpolluted areas ( Grzywacz et al 2012 ). Conversely, in a study by Giska et al (2015) , the highest genetic diversity was observed in the rove beetle, Staphylinus erythropterus Linnaeus (Coleoptera: Staphylinidae), populations inhabiting a heavily metal-polluted site in southern Poland.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been documented that populations exposed to heavy metal pollution can exhibit varying responses, leading to either an increase or decrease in their genetic variation. An illustrative case can be found in the long-horned groundhopper, Tetrix tenuicornis (Sahlberg) (Orthoptera: Tetrigidae), where individuals collected from metal-polluted regions in Boleslaw, Poland, displayed reduced genetic variability compared to populations from unpolluted areas ( Grzywacz et al 2012 ). Conversely, in a study by Giska et al (2015) , the highest genetic diversity was observed in the rove beetle, Staphylinus erythropterus Linnaeus (Coleoptera: Staphylinidae), populations inhabiting a heavily metal-polluted site in southern Poland.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations that impede primer binding or otherwise interfere with the amplification process can reveal this variation when using the RAPD technique ( Butovskaia et al 2009 ). By evaluating DNA polymorphism, researchers can identify population genetic responses to toxicant exposure ( Grzywacz et al 2012 , Babu et al 2013 ). Therefore, the RAPD analysis employed in this study has the potential to detect genetic changes in A. thalassinus related to adaptation and response to pollution and contamination in their habitats.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This molecular marker has an advantage of the possibility of using a different set of primers and choosing the best for each analysis as different sets of primers often produce different banding patterns that can be used in a variety of studies (Yulin et al 1998, grutzmacher et al 2007, Johnson et al 2008, Zahoor et al 2013, Coelho-Bortolo et al 2016, Preet and gupta 2017. Therefore, these markers have several entomological applications, for example, in forensic entomology, breeding programs, taxonomic identification of pests of agronomic interests, detection of genetic variation among populations, as well as, in the identification of closely related species (Grzywacz et al 2012, ercan et al 2012, Sivasankaran et al 2013, Matta et al 2013, Sunitha et al 2015, Singh et al 2016, Haghighi and Kumar 2017, Queiroz et al 2017, Sharma and Singh 2017. With regard to species identification, the analysis of electrophoretic profiles has been used in other groups of insects, with satisfactory results (Yulin et al 1998, 1999, Johnson et al 2008, Sivasankaran et al 2013, Zahoor et al 2013, Bajpai 2016a.…”
Section: Discussionmentioning
confidence: 99%